2015
DOI: 10.1016/j.ahj.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Hospital variation in admission to intensive care units for patients with acute myocardial infarction

Abstract: Background The treatment of patients with acute myocardial infarction (AMI) was transformed by the introduction of intensive care units (ICUs), yet we know little about how contemporary hospitals employ this resource-intensive setting and whether higher use is associated with better outcomes. Methods We identified 114,980 adult hospitalizations for AMI from 311 hospitals in the 2009–10 Premier database using codes from the International Classification of Diseases, Ninth Revision, Clinical Modification. Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
58
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 43 publications
0
58
2
Order By: Relevance
“…35 The NCDR collected data on each patient’s MI type, hemodynamic status, troponin level, and other covariates allowing for the calculation of mortality risk on admission; thus it extends these prior findings by offering a unique perspective of how illness severity may factor into ICU utilization. While the majority of STEMI patients (80%) are treated in an ICU, 4 hospitals varied substantially in the location of care for older NSTEMI patients. There were no significant differences in hospital characteristics (including size, teaching status, and revascularization capability) across high, intermediate, and low ICU utilization hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…35 The NCDR collected data on each patient’s MI type, hemodynamic status, troponin level, and other covariates allowing for the calculation of mortality risk on admission; thus it extends these prior findings by offering a unique perspective of how illness severity may factor into ICU utilization. While the majority of STEMI patients (80%) are treated in an ICU, 4 hospitals varied substantially in the location of care for older NSTEMI patients. There were no significant differences in hospital characteristics (including size, teaching status, and revascularization capability) across high, intermediate, and low ICU utilization hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that ICU admission rates vary widely for all-comers [24], patients with diabetic ketoacidosis [25], congestive heart failure [26], pulmonary embolism [27], and acute myocardial infarction [28]. In these studies, despite wide variations in ICU admission rates, there was no difference in risk-adjusted mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable interhospital variability in intensive care unit (ICU) use has been observed for patients with non–ST‐segment–elevation myocardial infarction (NSTEMI) . ICU use is only minimally correlated with severity of illness, with many low‐risk patients treated in the ICU and many high‐risk patients not treated in the ICU .…”
mentioning
confidence: 99%
“…In one study, 41% of patients with NSTEMI with a predicted risk of in‐hospital mortality <1% were treated in the ICU, and more than half of patients with initial serum troponin elevations >10 times the institution's upper limit of normal were not treated in an ICU . Given non–risk‐driven use patterns, it is perhaps unsurprising that higher hospital‐level ICU use is not associated with lower patient mortality …”
mentioning
confidence: 99%
See 1 more Smart Citation